Pengaruh Pemberian Buah Kurma Ajwa Terhadap Penurunan Morning Sickness Pada Ibu Hamil Trimester I - Purnamasari, Indah; Agustina, Indah Fitri; Kanah, Neneng; Hanifa, Fatya Nurul (SAMODRA ILMU: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2023)
Background: The number of incidents of nausea and vomiting reaches 12.5% of the number of pregnancies in the world. In Indonesia there are 50-90% cases of nausea and vomiting experienced by pregnant women. Nearly 50-90% of pregnant women experience nausea and vomiting in the first trimester. Morning Sickness is a natural symptom that occurs in pregnant women, but this symptom can be dangerous if the symptoms get worse to become Hyperemesis Gravidarum or which can result in the death of the mother and the fetus she is carrying. Complications of nausea and vomiting are dehydration and malnutrition. Objective: To determine the effect of giving ajwa dates to reduce morning sickness in first trimester pregnant women at PBM Ny. L Bolenglang, Ciamis Regency. Methods: This type of research is quantitative, namely pre-experimental with a one-group pre-test-post-test design. The sample was divided into two groups: the experimental group which was given ajwa dates and the control group without ajwa dates. Results: statistical test results using the T test obtained a tcount value of 2.104 when compared to the ttable value (1.761) then the tcount value is greater than ttable (2.104 > 1.761), then H0 is rejected. Conclusion: There is an effect of giving ajwa dates on reducing morning sickness in first trimester pregnant women at PBM Ny.L Bolenglang, Ciamis Regency.